2013
DOI: 10.1155/2013/205284
|View full text |Cite
|
Sign up to set email alerts
|

The Serum IL-6 Profile and Treg/Th17 Peripheral Cell Populations in Patients with Type 1 Diabetes

Abstract: IL-6 is a pleiotropic cytokine involved in the regulation of the immune response, inflammation, and hematopoeisis. Its elevated levels are found in a range of autoimmune and chronic inflammatory diseases. IL-6 is also involved in regulation of the balance between two T cell subsets: Tregs and Th17, which have contradictory functions in the control of inflammation. The present study provides a quantitative analysis regarding the Th17/Treg cell balance in peripheral blood of children with type 1 diabetes and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…Some reported high production of Th1 cytokines and low production of Th2 cytokines in T1D [311], confirming results from animal studies [305], while others detected low production of Th1 cytokines in peripheral blood [312]. Furthermore, up-regulation of the Th17 cell associated cytokine IL-17 has been reported in peripheral blood of T1D patients [313][314][315][316]. …”
Section: Development Of T1d/(molecular) Pathogenesissupporting
confidence: 56%
“…Some reported high production of Th1 cytokines and low production of Th2 cytokines in T1D [311], confirming results from animal studies [305], while others detected low production of Th1 cytokines in peripheral blood [312]. Furthermore, up-regulation of the Th17 cell associated cytokine IL-17 has been reported in peripheral blood of T1D patients [313][314][315][316]. …”
Section: Development Of T1d/(molecular) Pathogenesissupporting
confidence: 56%
“…Our previous studies suggested that inflammation associated with long-lasting T1DM was responsible for such an effect on Tregs. These cells were characterized by decreased expression of FoxP3 and CD62L under proinflammatory conditions, and this effect could be reverted using anti-inflammatory agents [16–19]. It was intriguing that, in the current study, gradual increase in the level of proinflammatory cytokines was seen early, starting from the clinical onset of T1DM.…”
Section: Discussionmentioning
confidence: 76%
“…In fact, besides an increase of circulating Th17 cells, a reduction of Treg cells in the peripheral blood of patients with T1D has also been reported [46].…”
Section: Discussionmentioning
confidence: 94%